The Role of Teachers’ Constructivist Beliefs in Classroom Observations: A Social Cognitive Theory Perspective - Chen, Po-Hsi; Hong, Jon-Chao; Ye, Jian-Hong; Ho, Ya-Jiuan (Frontiers in Psychology, 2022)
Previous studies have focused on individuals learning from observing a model to be able to produce the modeled behavior. However, there is a lack of studies emphasizing the perspective of being observed to understand the role of perceived value and stress when teachers act as a teaching model. To address this gap, the present study explored the correlates between teachers’ teaching beliefs, perceived value, psychosocial stress, and continuous intention to be the observed teaching model in classroom observations. Data of 349 respondents were usefully collected, and confirmatory factor analysis with structural equation modeling was performed. Results showed that teachers’ constructivist belief in teaching was positively related to perceived value of being observed and getting feedback, but was negatively related to psychosocial stress. Perceived value was positively related to continuous intention to be observed in future classroom observations, but perceived psychosocial stress was not significantly related to continuous intention. The results of this study can be applied to encourage those who are resistant to presenting their teaching experience in classroom observations.